PENGARUH STATUS SOSIAL EKONOMI DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR IPS - Yopi Nisa Febianti; Faizah Hijriati; Endang Herawan (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
The research aimed to prove the influence of socio-economic status and parental attention on students' social studies learning achievement at SMPN 1 Plumbon. The approach used is a quantitative approach. data collection using questionnaires, interviews and documentation. The population in the study were all students at SMPN 1 Plumbon, the sample in this study was class VIII as many as 80 students at SMPN 1 Plumbon using random sampling. The data analysis technique in this research uses multiple linear regression analysis with the help of SPSS version 25 software. The results of this research show that parental attention has a significant effect on students' social studies learning achievement. Apart from that, the variable parental attention has a more dominant influence compared to socio-economic status as seen from the results of the Standardized Coefficient Beta, parental attention has the highest value of 0.383 compared to socio-economic status. With this research, it is hoped that it will be useful for parents, teachers, and school